Research progress of nutritional interventions for patients undergoing hematopoietic stem cell transplantation (造血干细胞移植患者营养干预模式研究进展) - WANG Xu (王旭) (Journal of International Translational Medicine Limited, 2024)
Hematopoietic stem cell transplantation (HSCT) has been widely used in the treatment of malignant hematological diseases, non-malignant refractory hematological diseases and some solid tumors. Preconditioning of HSCT will inevitably cause damage to the gastrointestinal tract and increase the incidence of malnutrition. Malnutrition can affect hematopoietic reconstitution, increase the incidence of acute graft-versus-host disease (aGVHD) and infection, and prolong hospital stay. At present, there are few reports on systematic nutritional intervention in patients with hematopoietic stem cell transplantation. This article reviewed the nutritional risk screening and assessment tools, nutritional support methods and nutritional intervention models for patients undergoing HSCT, and provided reference for establishing related nutritional plan. (造血干细胞移植(HSCT)被广泛应用于恶性血液病、非恶性难治性血液病和某些实体瘤的治疗。HSCT预处理会对胃肠道造成不可避免的损伤, 增加营养不良风险。营养不良会影响造血功能重建, 增加急性移植物抗宿主病( aGVHD)及感染的发生率, 延长住院时间, 严重影响HSCT患者生存质量。本研究就HSCT患者营养风险筛查和评估工具、营养支持方式及营养干预模式进行综述, 旨在为HSCT患者营养干预方案的制定提供参考。)